Ibutilide for the Cardioversion of Paroxysmal Atrial Fibrillation during Radiofrequency Ablation of Supraventricular Tachycardias. (24th May 2011) - Polymeropoulos, Kostas; Vassilikos, Vassilios P.; Mantziari, Lilian; Paraskevaidis, Stelios; Karamitsos, Theodoros D.; Mochlas, Sotirios; Parcharidis, Georgios; Louridas, Georgios; Styliadis, Ioannis H.
Abstract : Direct current electrical cardioversion (DC-ECV) is the preferred treatment for the termination of paroxysmal atrial fibrillation (AF) that occurs during radiofrequency ablation (RFA) of supraventricular tachycardias (SVT). Intravenous Ibutilide may be an alternative option in this setting. Thirty-four out of 386 patients who underwent SVT-RFA presented paroxysmal AF during the procedure and were randomized into receiving ibutilide or DC-ECV. Ibutilide infusion successfully cardioverted 16 out of 17 patients (94%) within17.37 ± 7.87  min. DC-ECV was successful in all patients (100%) within17.29 ± 3.04  min. Efficacy and total time to cardioversion did not differ between the study groups. No adverse events were observed. RFA was successfully performed in 16 patients (94%) in the ibutilide arm and in all patients (100%) in the DC-ECV arm, p = NS. In conclusion, ibutilide is a safe and effective alternative treatment for restoring sinus rhythm in cases of paroxysmal AF complicating SVT-RFA.